2004
DOI: 10.1086/421122
|View full text |Cite
|
Sign up to set email alerts
|

Increased Replication of HIV‐1 Minor Variants during Hematopoietic Stem‐Cell Mobilization with Filgrastim

Abstract: The hypothesis that filgrastim (r-met-huG-CSF) activates replication of minor variants of human inmmunodeficiency virus type 1 (HIV-1) was tested by analysis of plasma quasi-species composition in 7 subjects in whom plasma HIV-1 RNA had increased during filgrastim treatment. Inferred phylogenetic trees of env sequences from 3 subjects during filgrastim treatment contained unique intrasubject subclusters that shared a most recent common ancestor with the baseline HIV-1 quasi species. Genotypes in the unique sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…Although there are several mechanisms by which G-CSF treatment could stimulate HIV replication [9], our results showed that HIV load wasn't consistently affected by the G-CSF in patients with severe immune depletion under HAART.…”
Section: Resultscontrasting
confidence: 58%
“…Although there are several mechanisms by which G-CSF treatment could stimulate HIV replication [9], our results showed that HIV load wasn't consistently affected by the G-CSF in patients with severe immune depletion under HAART.…”
Section: Resultscontrasting
confidence: 58%
“…Because the majority of the information on the effects of G-CSF on lymphocyte functions and HIV life cycle were initially based on in vitro data, in vivo measurements were rapidly needed. Campbell et al (24) suggested that in HIV-positive subjects undergoing stem cell mobilization, G-CSF produced transient, although measurable, increases of HIV RNA plasma levels consistent with its ability to promote in vitro active viral replication. On the contrary, HIV DNA levels remained stable, suggesting that the viral reservoir was not substantially modified after the administration of the cytokine.…”
Section: Immunological and Virological Aspects Of Apsctmentioning
confidence: 99%